Antigen-Presenting Cells in the Airways: Moderating Asymptomatic Bacterial Carriage - Lisa J. M. Slimmen; Hettie M. Janssens; Annemarie M. C. van Rossum; Wendy W. J. Unger (Pathogens, 2021)
Bacterial respiratory tract infections (RTIs) are a major global health burden, and the role of antigen-presenting cells (APCs) in mounting an immune response to contain and clear invading pathogens is well-described. However, most encounters between a host and a bacterial pathogen do not result in symptomatic infection, but in asymptomatic carriage instead. The fact that a pathogen will cause infection in one individual, but not in another does not appear to be directly related to bacterial density, but rather depend on qualitative differences in the host response. Understanding the interactions between respiratory pathogens and airway APCs that result in asymptomatic carriage, will provide better insight into the factors that can skew this interaction towards infection. This review will discuss the currently available knowledge on airway APCs in the context of asymptomatic bacterial carriage along the entire respiratory tract. Furthermore, in order to interpret past and futures studies into this topic, we propose a standardized nomenclature of the different stages of carriage and infection, based on the pathogen’s position with regard to the epithelium and the amount of inflammation present.